Spatial Proximity in Venture Capital Financing A Theoretical and Empirical Analysis of Germany - Bender, Marko; SpringerLink (Online service) (Wiesbaden : Gabler, 2011)
Marko Bender analyzes the impact of spatial proximity between venture capitalists and new ventures throughout the investment process. He elaborates a comprehensive theoretical framework and empirically validates resulting hypotheses concerning the observed spatial proximity and the impact of spatial proximity on the likelihood of a venture capital investment using a German dataset. A thorough discussion of results and resulting implications for entrepreneurs, venture capitalists, and public policy concludes this thesis.
Keywords: Economics; Banks and banking; Economics/Management Science; Finance /Banking.